1995
DOI: 10.1002/jbm.820290712
|View full text |Cite
|
Sign up to set email alerts
|

Mixed‐metal fretting corrosion of Ti6Al4V and wrought cobalt alloy

Abstract: Corrosion has been reported at the modular interfaces of total joint replacement implants, but with conflicting theories as to the cause of such damage. The modular design itself leaves the interface susceptible to galvanic, crevice, or fretting corrosion, or a combination of the three. The purpose of this study was to quantify the effect of material combination on fretting corrosion of orthopedic alloys. Each test specimen consisted of a two-hole plate with spherical countersinks and two cortical bone screws.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 15 publications
2
43
0
Order By: Relevance
“…The literature unequivocally demonstrates that design-and material-related parameters influence micro-motion and [8,9,11,13,15]. However, no differences in total titanium release were found for the implant designs tested here.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The literature unequivocally demonstrates that design-and material-related parameters influence micro-motion and [8,9,11,13,15]. However, no differences in total titanium release were found for the implant designs tested here.…”
Section: Discussionmentioning
confidence: 54%
“…A similar study on a modular neck hip implant design made of a titanium alloy revealed material loss of between 280 and 1,640 µg after 5.5×10 6 loading cycles [22]. Another study on a titanium plate-screw connection resulted in a titanium release of 849 µg after 1.2×10 6 loading cycles [13]. Lower concentrations ranging from 3 to 21 µg were also reported for plate-screw connections [11].…”
Section: Discussionmentioning
confidence: 82%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Initially, corrosion was thought to result from a galvanic process due to the coupling of Ti-6Al-4V alloy with CoCrMo alloy. 2 This hypothesis was rejected by the finding of comparable corrosion products in similar alloy (CoCrMo/CoCrMo) couples.…”
Section: Introductionmentioning
confidence: 99%
“…10 Other variables include local environmental conditions, such as pH and the presence of proteins in the modular junction. 1,11,12 Crevice, galvanic, and fretting corrosion are all possible in modular junctions.…”
Section: Introductionmentioning
confidence: 99%
“…about fretting and crevice corrosion at the modular taper junction, particularly with mixed-metal junctions, were reported 4,[6][7][8][9][10] . Subsequent design and manufacturing improvements minimized these concerns, allowing a nearly universal adoption of modular femoral head-neck tapers in modern total hip arthroplasty.…”
mentioning
confidence: 99%